Unsupervised Detection of Cell-Assembly Sequences by Similarity-Based Clustering - Watanabe, Keita; Haga, Tatsuya; Tatsuno, Masami; Euston, David R.; Fukai, Tomoki (Frontiers in Neuroinformatics, 2019)
Neurons which fire in a fixed temporal pattern (i.e., ``cell assemblies'') are hypothesized to be a fundamental unit of neural information processing. Several methods are available for the detection of cell assemblies without time structure. However, the systematic detection of cell assemblies with time structure has been challenging, especially in large datasets, due to the lack of efficient methods for handling the time structure. Here, we show a method to detect a variety of cell-assembly activity patterns recurring in noisy neural population activity at multiple timescales. The key innovation is the use of a computer science method for comparing strings (``edit similarity'') to group spikes into assemblies. We validated the method by using artificial data and experimental data, which were previously recorded from the hippocampus of male Long-Evans rats and the prefrontal cortex of male Brown Norway/Fisher hybrid rats. From the hippocampus, we could simultaneously extract place-cell sequences occurring on different timescales during navigation and awake replay. From the prefrontal cortex, we could discover multiple spike sequences of neurons encoding different segments of a goal-directed task. Unlike conventional event-driven statistical approaches, our method detects cell assemblies without creating event-locked averages. Thus, the method offers a novel analytical tool for deciphering the neural code during arbitrary behavioral and mental processes.